1999
DOI: 10.1038/23488
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal mast cells in mice deficient in a heparin-synthesizing enzyme

Abstract: Heparin is a sulphated polysaccharide, synthesized exclusively by connective-tissue-type mast cells and stored in the secretory granules in complex with histamine and various mast-cell proteases. Although heparin has long been used as an antithrombotic drug, endogenous heparin is not present in the blood, so it cannot have a physiological role in regulating blood coagulation. The biosynthesis of heparin involves a series of enzymatic reactions, including sulphation at various positions. The initial modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
408
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(423 citation statements)
references
References 26 publications
13
408
0
2
Order By: Relevance
“…In contrast, the ratios of the N -deacetylation and N -sulfation activities between NDST-1 and -2 were similar (72). Notably, mice carrying a targeted disruption of NDST-2 are unable to synthesize heparin but can produce HS (73,74), whereas those of NDST-1 synthesize lowsulfated variant of HS resulting in embryonic lethality (75,76). The NDST isoforms have distinct expression levels in different mouse tissues (72).…”
Section: Biosynthetic Events Modifiying the Glycosylaminoglycan Backbonementioning
confidence: 88%
“…In contrast, the ratios of the N -deacetylation and N -sulfation activities between NDST-1 and -2 were similar (72). Notably, mice carrying a targeted disruption of NDST-2 are unable to synthesize heparin but can produce HS (73,74), whereas those of NDST-1 synthesize lowsulfated variant of HS resulting in embryonic lethality (75,76). The NDST isoforms have distinct expression levels in different mouse tissues (72).…”
Section: Biosynthetic Events Modifiying the Glycosylaminoglycan Backbonementioning
confidence: 88%
“…Ndst2 −/− and Srgn −/− mast cells shared several characteristics, such as decreased storage of granule proteases with Hdc −/− mast cells and it was concluded that major defects in granule maturation in Ndst2 −/− and Srgn −/− cells should occur at the posttranslational levels; impaired accumulation of sulfated proteoglycans might lead to instability of the granule proteases in Ndst2 −/− and Srgn −/− mast cells. Histamine contents in pMCs of Hdst2 −/− and Srgn −/− mice were found to be significantly decreased [23,25], although it remains unknown whether expression of the Hdc gene is suppressed or granule storage of histamine is impaired in these cells due to the absence of sulfated proteoglycans. A decrease in histamine synthesis may also be involved in the aberrant granule maturation in Hdst2 −/− and Srgn −/− mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is critical because sulfation patterns within HS chains govern their ability to bind and influence the activity of soluble and matrix proteins including key factors, for example, members of the fibroblast growth factor (FGF) family [8,9]. Mice mutant for many components of the biosynthetic pathway have demonstrated that the majority of modifications are critical for successful development [10][11][12][13]. HS-deficient mice were created by deleting either Ext1 or Ext2 [14,15], and the pregastrulation lethality of the phenotypes indicates a critical need for HS in tissue organization and migration.…”
Section: Introductionmentioning
confidence: 99%